Digital entrepreneurship - Allen, Jonathan P., ....- (New York : Routledge, Taylor and Francis Group, 2019)
Technology has enabled a new age of entrepreneurship as entrepreneurs find digital tools that enable new ventures to exploit commercial opportunities around the world. This textbook provides students with expert guidance on using technology platforms to start new ventures. With an award-winning approach, the author guides readers through the process of a lean startup, taking a digital first approach to entrepreneurship. Students using the book will emerge with enhanced understanding of different digital business models, analytical skills for digital ventures, and the confidence to move from prototype to product. Online resources such as slides, a sample syllabus, and exercises encourage the classroom to become an interactive and dynamic space.
Includes index.
Description based on print version record.
Keywords: Entrepreneurship; Ondernemen ; innovatie